Performance Analysis of Kudzu Fiber Prepared by Using Combined Steam Explosion and Chemical Degumming - Yan Song; Guangting Han; Minghua Li; Wei Jiang; Xianbo Li; Yuanming Zhang; Renxia Yu (Journal of Natural Fibers, 2017)
Kudzu is cosmopolitan and low-cost as a source of fiber, food, medicine, and fuel. However, it is not well utilized as a kind of fiber due to the degumming problem. In order to take full advantage of the kudzu resource in the world and expand the application field of kudzu fiber, this study deals with preparation of kudzu fiber by combined steam explosion and chemical degumming. Kudzu fibers are characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, and X-ray diffraction. It is found that kudzu fiber after combined degumming has a clean surface with most nonfibrous composition removed and fibers dispersed; the cellulose I structure of kudzu cellulose did not change after treatment but its crystallinity increased. These results suggest this combined degumming is feasible for preparing kudzu fiber. It will probably provide theoretical basis for subsequent utilization of kudzu fibers.